Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO

Fe-doped SnO(2) nanomaterial: a low temperature hydrogen sulfide gas sensor - Vaishampayan, Mukta V.; Deshmukh, Rupah G.; Walke, Pravin; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2008)
The effect of Fe-doping on the surface chemistry and gas-sensing properties of nanocrystalline tin oxide is analyzed. The pristine and Fe-doped SnO(2) are synthesized by the modified Pechini citrate route that produces around 40 and 18 nm sized nanoparticles, respectively. 1 at.% Fe-doped SnO(2) shows significantly high selectivity towards hydrogen sulfide gas with capability to detect even 10 ppm of hydrogen sulfide at room temperature, with change of about one order of magnitude in the resistance within 5-15 s. In comparison, pristine SnO(2) shows negligible response towards H(2)S at room temperature. The ideal response and recovery of Fe-doped SnO(2) at low concentration of gas suggests Fe-doped SnO(2) nanomaterial as a potential low cost, low temperature H(2)S gas sensor. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Fe-doping; H(2)S; nanomaterial; Sensor; tin oxide

Nanostructured nickel ferrite: a liquid petroleum gas sensor - Darshane, Sonali L.; Suryavanshi, S. S.; Mulla, Imtiaz S. (Ceramics International, 2009)
The present investigation deals with the synthesis of nanostructured nickel ferrite (NiFe(2)O(4)) and their liquid petroleum gas-sensing characteristics. The 15-20 nm size nickel ferrite has been synthesized at 700 degrees C by a simple molten-salt route using sodium chloride as grain growth inhibitor. These nanoparticles exhibit significantly high response towards liquid petroleum gas (LPG) in comparison with ethanol vapor, hydrogen sulfide, ammonia and hydrogen. The gas response towards various gases at their 200 ppm concentrations is investigated at 200-450 degrees C. Different characterization techniques have been employed, such as differential thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) to study the crystallite size, structure and morphology. The results suggest possibility of utilization of the nanostructured nickel ferrite, without addition of any precious metal ion, as the LPG detector. (c) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrites; nanomaterial; Sensor; Spinels

Acetone vapour sensing characteristics of undoped and Zn, Ce doped SnO2 thick film gas sensor - Bagal, L. K.; Patil, J. Y.; Bagal, K. N.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Materials Research Innovations, 2013)
The nanocrystalline materials of zinc and ceria doped tin oxide [(Zn+Ce)-SnO2] powders were synthesised by coprecipitation method and investigated for their sensing properties towards liquid petroleum gas (LPG), ethanol, ammonia and acetone vapour. The crystal structure and phase of the as synthesised and sintered powders were characterised by X-ray diffractometer and the microstructure by scanning electron microscopy. All the doped and undoped SnO2 compositions revealed single phase solid solution formation. Transmission electron microscope results indicated that well crystallised (Zn+Ce) doped SnO2 particles of size similar to 7 nm were obtained at the annealing temperature of 650 degrees C. The reduction in grain size of the metal oxide is a key factor to enhance the gas sensing properties. The doping of zinc, ceria in SnO2 has reduced the grain size and improved the gas response. The results of gas sensing measurements showed that the thick films deposited on alumina substrates using screen printing technique exhibited high response to acetone at an operating temperature of 300 degrees C. Further, the selectivity of the sensor towards acetone with respect to other reducing gases (LPG, ethanol and ammonia) was studied.
Keywords: Gas; Screen printing; Sensor; SnO2

Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

H2S detection using low-cost SnO2 nano-particle Bi-layer OFETs - Surya, Sandeep G.; Ashwath, B. S. Narayan; Mishra, Sushma; Karthik, A. R. B.; Sastry, A. B.; Bhagavatula L. V. Prasad; Rangappa, Dinesh; Rao, V. Ramgopal (Sensors and Actuators B-Chemical, 2016)
In this article, a unique platform with an organic field-effect transistor (OFET) integrated with metal oxide nanoparticles for sensing of H2S gas is presented. Metal oxide nanoparticles such as SnO2 and ZnO synthesized using herbal techniques were used in the fabrication of OFETs using a bi-layer technique. The as -synthesized nanoparticles were characterized by Field Effect Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and UV-vis Spectroscopy (UV-vis) to establish the material properties. We showed that the SnO2 based OFETs displayed better response for H2S at room temperature (25 degrees C) compared to the OFETs fabricated with ZnO. The characterization of the sensors by using extracted electrical parameters like field-effect mobility ([1), On -Current (Ion), threshold voltage (VT) and saturation current (ID]) establish the fact that the SnO2 based OFETs detect H2S gas at room temperature. Plausible mechanisms explaining the H2S gas detection by bi-layer film were discussed. On the other hand, the sensitivity of these OFETs against other reducing gases was less. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: bi-layer; H2S detection; Metal-oxide; OFETs; Sensor

Temperature-dependent Raman spectroscopy and sensor applications of PtSe2 nanosheets synthesized by wet chemistry - Pawar, Mahendra S.; Late, Dattatray J. (Beilstein Journal of Nanotechnology, 2019)
We report on a wet chemistry method used to grow PtSe2 nanosheets followed by thermal annealing. The SEM and TEM analysis confirms the formation of PtSe2 nanosheets. Furthermore, XRD, Raman, XPS and SAED patterns were used to analyze the crystal structure and to confirm the formation of the PtSe2 phase. The temperature-dependent Raman spectroscopy investigations were carried out on PtSe2 nanosheets deposited on Si substrates in the temperature range 100-506 K. The shifts in Raman active E-g and A(1g) modes as a function of temperature were monitored. The temperature coefficient for both modes was calculated and was found to match well with the reported 2D transition metal dichalcogenides. A PtSe2 nanosheet-based sensor device was tested for its applicability as a humidity sensor and photodetector. The humidity sensor based on PtSe2 nanosheets showed an excellent recovery time of approximate to 5 s, indicating the great potential of PtSe2 for future sensor devices.
Keywords: nanosheets; PtSe2; Raman spectroscopy; Sensor; thermal effect

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration

Hexagonal boron nitride quantum dots embedded on layer-by-layer films for peroxidase-assisted colorimetric detection of β-galactosidase producing pathogens - Majumdar, Sristi; Gogoi, Devipriya; Boruah, Purna K.; Thakur, Ashutosh; Sarmah, Priyakhee; Gogoi, Parishmita; Sarkar, Sanjib; Pachani, Priyakshi; Manna, Prasenjit; Saikia, Ratul; Chaturvedi, Vikash; Shelke, Manjusha V.; et al. (ACS Applied Materials and Interfaces, 2024)
Pathogen detection has become a major research area all over the world for water quality surveillance and microbial risk assessment. Therefore, designing simple and sensitive detection kits plays a key role in envisaging and evaluating the risk of disease outbreaks and providing quality healthcare settings. Herein, we have designed a facile and low-cost colorimetric sensing strategy for the selective and sensitive determination of beta-galactosidase producing pathogens. The hexagonal boron nitride quantum dots (h-BN QDs) were established as a nanozyme that showed prominent peroxidase-like activity, which catalyzes 3,3 `,5,5 `-tetramethylbenzidine (TMB) oxidation by H2O2. The h-BN QDs were embedded on a layer-by-layer assembled agarose biopolymer. The beta-galactosidase enzyme partially degrades beta-1,4 glycosidic bonds of agarose polymer, resulting in accessibility of h-BN QDs on the solid surface. This assay can be conveniently conducted and analyzed by monitoring the blue color formation due to TMB oxidation within 30 min. The nanocomposite was stable for more than 90 days and was showing TMB oxidation after incubating it with Escherichia coli (E. coli). The limit of detection was calculated to be 1.8 x 10(6) and 1.5 x 10(6) CFU/mL for E. coli and Klebsiella pneumonia (K. pneumonia), respectively. Furthermore, this novel sensing approach is an attractive platform that was successfully applied to detect E. coli in spiked water samples and other food products with good accuracy, indicating its practical applicability for the detection of pathogens in real samples.
Keywords: biopolymer; colorimetric; h-BN quantum dots; nanozyme; pathogens; Sensor